The Personality of Luqman Al-Hakim in the Holy Quran - Hassan , Ahmad (Islamic Sciences Journal, 2023)
ABSTRACT The description of the typical image was repeated in several parts of the Holy Qur’an, including what was mentioned in the biography of the previous ones, and among them is Luqman, who explained the features of the model personality in his commandments to his son. My interest in the manifestation of the typical personality me in light of the Quranic perception stems from the big gap between this personality and what we see in the personality of Muslim today. Perhaps this comparison will motivate to trace the steps of the ancestors, on the one hand and to identify some of the typical personality features as portrayed by the commandments of luqman to his son in the Noble Qur’an..